Prenatal Period and Infancy: Psychological Insights Into the Beginning of Life - Rzechowska, Ewa (Social and Personality Development in Childhood, 2025)
This chapter’s focus is on the emergence and development of human psychological life and a child’s bonding with the caregiver (mother) in the prenatal, postnatal and infancy periods. Developmental changes are presented from the very onset of life to familiarise non-psychologists working with children with their nature and mechanisms.Biological transformations and the first signs of foetus’s motor and sensory activity occurring in the prenatal period create a setting for the development of early mental activity, memory and various forms of learning, as well as of the neurohormonal, behavioural and psychological communication required for a child to bond with its mother.Newborns’ innate sensitivity to various forms of stimulation from people preadapts them to social contacts. In the first 12 months of life, they develop locomotor skills and an integrated perception of their environment, transition from ‘thinking in acting’ fed by sensory data to increasingly purposeful and intentional activities and stabilise their image of the world. As a result of interactions with the caregiver(s), they acquire the ability of pre-verbal communication, experiencing and recognising emotions and building a common space of meanings and actions.A child’s basic trust is formed based on its early experiences with caregivers. The quality of its bond with the caregiver translates into the type of attachment behaviour it will show (secure, anxious-ambivalent, anxious-avoidant and disoriented-disorganised attachment). Trust and attachment are significant for a child’s readiness for exploratory activity and the onset of self-regulation.Keywords: prenatal period, newborn, infancy, child development, preadaptation, trust, attachment styles